Devoted fans release more cortisol when watching live soccer matches. (5th February 2020) - Newson, Martha; Shiramizu, Victor; Buhrmester, Michael; Hattori, Wallisen; Jong, Jonathan; Yamamoto, Emilia; Whitehouse, Harvey
Abstract: Why do some sports fans experience intense emotions when watching live matches? Identity fusion is a strong form of group alignment in which personal and group identities are activated synergistically to produce a visceral sense of 'oneness' with one's team. Here we examine the role of fusion (using a three‐item state measure with high internal validity) in elevating salivary cortisol levels while watching football ( n = 41). Our evidence was gathered at field laboratories during the 2014 sFIFA World Cup in Natal, Brazil, with live screenings of two Brazilian victories (Colombia, 2–1; Chile, 1–1 with penalties), and the historic semi‐final loss to Germany (1–7). We replicated previous studies showing that salivary cortisol concentrations fluctuate during live football events and are related to group membershipbut we also extended them by showing that identity fusion is even more strongly related to cortisol concentrations than identification. We found an interaction between match outcome and cortisol, such that watching a loss, i.e. dysphoria, was associated with particularly high cortisol concentrations. While women were more fused to the team than men, there were no other gender effects. Taken together, these findings suggest that identity fusion modulates physiological reactivity, resulting in distinct psycho‐physiological profiles during stressful events.